Academic Service Quality Analysis In Walisongo UIN FITK, Semarang - Wahyudi Wahyudi; Sri Wulandari (Indonesian Academy of Social and Religious Research (IASRR), 2023)
This study aims to analyze the quality of academic services at the Faculty of Tarbiyah and Teacher Training (FITK) at the Walisongo State Islamic University (UIN) Semarang. This type of research is called mixed research (mix method), which seeks to examine a subject in depth using qualitative and quantitative methods. This in-depth study is intended to form a model or theory based on the interrelationships between the data found. Broadly speaking, there are two types of data used in this study, namely, primary data and secondary data. First, primary data were obtained from study program leaders at the Faculty of Tarbiyah and Teacher Training. This data was obtained using data collection techniques, namely questionnaires, interviews, and focus group discussions. Second, secondary data obtained from collecting and observing documents related to the quality of academic services The results of this study can be summarized as follows: 1) The quality of academic services at the Faculty of Tarbiyah and Teacher Training (FITK) at Walisongo State Islamic University (UIN) Semarang is good. This is based on the average score of academic service quality, 80.43%; 2) The five dimensions of academic service quality, Faculty of Tarbiyah and Teacher Training (FITK) at Walisongo State Islamic University (UIN) Semarang prioritize the tangible dimension.